A Combination of Interpolation and Spatial Correlation Technique to Estimate the Channel in Wideband MIMO-OFDM System - Nguyen, Thu Nga; Nguyen, Van Duc (Old Journal, 2019)
In this paper, we combine the interpolation and the spatial correlation techniques to estimate the channel coefficient in wideband multi-input multi-output orthogonal frequency division multiplexing (MIMO-OFDM) system. The simulation is based on the measurement channel modelling method - the Spatial Channel Model (SCM) in the suburban macrocell and microcell environment, under the LTE Advanced standard for 4G. The obtained results show symbol error rate (SER) value when using both different interpolation methods (Linear, Sinc Interpolation-SI and Wiener) and spatial correlation coefficients. The SER results in the SCM channel model are shown that the more of the window step of the interpolation, the worse of the performance system is, as well as, the effect of estimating channel is improved by increasing the distance of antenna element in BS side. Moreover, we can also conclude that of the three interpolation methods, the Wiener interpolation has the best system’s performance.